How to get tenured - Michael Graber; Andrey Launov; Klaus Waelde (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2007)
Getting a tenured position in economics in Germany is viewed as a random outcome where the probability of tenure depends on the quantity and qual- ity of publications, age and years since PhD. We measure publications both in units of Top 5 journals and in units of the European Economic Review (EER). We find that the average age of a professor in the year of his first appointment in Germany in the period of 1970 to 2005 is 38. This is ap- proximately 8 years after the PhD. He has 1.5 standardized Top 5 papers or 2.2 standardized EER papers, i.e. written with one coauthor and of 20 pages length. Results vary across subfields and over time. Someone aiming for a tenured job after 2010 should by then (average over all fields) have 3.3 standardized Top 5 papers or 5 standardized EER papers.
Keywords: 330